2021
DOI: 10.1155/2021/5584268
|View full text |Cite
|
Sign up to set email alerts
|

Local Drug Delivery Systems for Vital Pulp Therapy: A New Hope

Abstract: Vital pulp therapy (VPT) is deliberated as an ultraconservative/minimally invasive approach for the conservation of vital pulpal tissues, preservation of dental structure, and maintenance of tooth function in the oral cavity. In VPT, following the exposure of the dental pulp, the environment is prepared for the possible healing and probable refunctionalisation of pulpal connective tissue. However, to succeed in VPT, specific biomaterials are used to cover and/or dress the exposed pulp, lower the inflammation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 113 publications
0
8
0
Order By: Relevance
“…These monomers are metabolized in the body through the tricarboxylic acid cycle, and the final metabolites, carbon dioxide and water, have no toxic effect on cells [ 62 , 63 , 64 , 65 ]. PLGA and PLLA can be used as suitable microcarriers to achieve sustained drug release [ 66 , 67 ]. As a scaffold material, PLGA is conducive to the colonization of cells (such as SHED, DPSCs, and dental pulp fibroblasts), and on PLGA scaffolds, stem cells can differentiate into odontoblast-like cells and endothelial cells, producing tissues similar to dental pulp and dentin [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…These monomers are metabolized in the body through the tricarboxylic acid cycle, and the final metabolites, carbon dioxide and water, have no toxic effect on cells [ 62 , 63 , 64 , 65 ]. PLGA and PLLA can be used as suitable microcarriers to achieve sustained drug release [ 66 , 67 ]. As a scaffold material, PLGA is conducive to the colonization of cells (such as SHED, DPSCs, and dental pulp fibroblasts), and on PLGA scaffolds, stem cells can differentiate into odontoblast-like cells and endothelial cells, producing tissues similar to dental pulp and dentin [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 However, it has been recently shown that CH is not as effective as speculated against intracanal microorganisms and cannot be addressed as a strong antibacterial agent despite having an alkaline pH. 8 Therefore, different studies have investigated new drugs or combination of drugs with more efficient antimicrobial activity as appropriate replacements for CH, for example, antibiotics, to be employed in endodontic treatments. Triple antibiotics paste (TAP), a combination of ciprofloxacin, metronidazole, and minocycline, has been discussed in various investigations for use in regenerative endodontic protocols and disinfection of RCS.…”
Section: Introductionmentioning
confidence: 99%
“…In numerous studies, calcium hydroxide (CH) has been widely used as an intracanal medicament to combat regional microbiota 6,7 . However, it has been recently shown that CH is not as effective as speculated against intracanal microorganisms and cannot be addressed as a strong antibacterial agent despite having an alkaline pH 8 . Therefore, different studies have investigated new drugs or combination of drugs with more efficient antimicrobial activity as appropriate replacements for CH, for example, antibiotics, to be employed in endodontic treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Dental and periodontal care in restorative dentistry is superior when using biocompatible and biodegradable drug delivery systems to eradicate bacterial infection, restore wound, and guide bone regeneration because re-operation will not be carried out (1) and drug bioavailability will be boosted by the limited diffusion and degradation of the loaded drugs (2) . Osseous tissues including teeth are mainly constituted by ions of calcium (Ca 2+ ) and phosphate (PO 4…”
Section: Introductionmentioning
confidence: 99%